Association study of Bif-1 gene expression with histopathological characteristics and hormone receptors in breast cancer - Kazhaleh Mohammadi; Mahdieh Salimi; S. Abdolhamid Angaji; Arthur Saniotis; Foroozandeh Mahjoobi (BMC, 2022)
Abstract Background Breast cancer is a heterogeneous disease that has various clinical outcomes. Bax-interacting factor-1 (Bif-1) is a member of the endophilin B family that generates the pro-apoptotic BCL2-Associated X (BAX) protein in response to apoptotic signals. Lack of Bif-1 inhibits the intrinsic pathway of apoptosis and enhancements the risk of tumor genesis. The present study aimed to investigate the relationship between hormone receptors (ER, PR, and HER2) status and different levels of Bif-1 gene expression in breast cancer patients. Methods Bif-1 gene expression was evaluated in 50 breast cancer tumors and 50 normal breast mammary tissues using the SYBR Green real-time RT-PCR technique. Multivariate and univariate analyses were used to appraise the relationship between the prognostic significance of the Bif-1 gene using SPSS software. In this study, the Bif-1 was selected as a candidate for a molecular biomarker and its expression status in breast cancer patients with hormone receptors (ER, RR, and HER2) compared to patients without these hormone receptors. Results The study showed that the relative expression of the Bif-1 gene in tissues of patients with hormone receptors in breast cancer compared to those without hormone receptors was not statistically significant. The expression levels of the Bif-1 gene in different groups were evaluated for hormone receptor status. No significant relationship was found between the Bif-1 gene expression and hormone receptors (ER, PR, and HER2) (p > 0.05). Conclusion Bif-1 gene expression may be a useful prognostic marker in breast cancer.